2016
DOI: 10.1111/febs.13961
|View full text |Cite
|
Sign up to set email alerts
|

Maxed out macs: physiologic cell clearance as a function of macrophage phagocytic capacity

Abstract: The phagocytic clearance of host cells is important for eliminating dying cells and for the therapeutic clearance of antibody-targeted cells. As ubiquitous, motile and highly phagocytic immune cells, macrophages are principal players in the phagocytic removal of host cells throughout the body. In recent years great strides have been made in identifying the molecular mechanisms that control the recognition and phagocytosis of cells by macrophages. However, much less is known about the physical and metabolic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 144 publications
(217 reference statements)
2
56
0
Order By: Relevance
“…In contrast, intraepithelial macrophages located in prostatic lesions were mostly enlarged, rounded cells, containing numerous, and large autophagic vacuoles. It has been shown that engulfment of multiple targets induces molecular and morphological changes in macrophages, making them rounder in shape with less membrane extension, thus reducing their capacity to engulf new targets 48 . Such macrophage features corroborate our present findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, intraepithelial macrophages located in prostatic lesions were mostly enlarged, rounded cells, containing numerous, and large autophagic vacuoles. It has been shown that engulfment of multiple targets induces molecular and morphological changes in macrophages, making them rounder in shape with less membrane extension, thus reducing their capacity to engulf new targets 48 . Such macrophage features corroborate our present findings.…”
Section: Discussionsupporting
confidence: 91%
“…Such macrophage features corroborate our present findings. One possible mechanism for enhancing the degradation of excess cytoplasmic cargo by macrophages is the involvement of autophagic pathways, which would lead to the LC3‐associated phagocytosis 48 . Consistent with these events, the engorged macrophages were usually found in clusters within the prostate lesions and were proven positive for the autophagic‐specific marker LC3.…”
Section: Discussionmentioning
confidence: 85%
“…Phagocytosis of dying or dead cells by phagocytes such as macrophages is known as efferocytosis (Birge et al, 2016; Zent and Elliott, 2017). Removal of dead or dying cells by efferocytosis is critical for maintaining homeostasis and preventing inflammation and autoimmune reactions (Elliott and Ravichandran, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The CD45 transmembrane protein is a principal component of the negative feedback signal in both efferocytosis and ADCP. CD45 functions as a "do not eat me" signal when it couples with SIRPα receptors on macrophages [61]. Expulsed cancer cell nuclei no longer express CD45; therefore, there is no negative feedback signals for macrophage engulfment.…”
Section: Nuclear Expulsion and The Formation Of Cancer Fusion Cells (mentioning
confidence: 99%